Early Results after Exclusion of Popliteal Aneurysms with an Endoprosthesis - Noory, Elias; Böhme, Tanja; Beschorner, Ulrich; Jacques, Börries; Bürgelin, Karlheinz; Zürn, Christina; Zeller., Thomas (Cardiology and Cardiovascular Medicine, 2022)
Objectives: To evaluate safety and efficacy of endoprosthesis implantation for the exclusion of popliteal artery aneurysm (PAA). Methods: Elective asymptomatic patients with aneurysm > 20 mm and symptomatic patients with endovascular therapy of PAA were included. The proportion of patients with critical limb ischemia (presence of rest pain or tissue loss) was high at 32.1%, 21.6% of the patients had acute ischemia with symptoms persisting shorter than 14 days. The primary study endpoint was the target lesion revascularization (TLR) rate at 12 months. Secondary endpoints included technical success, periinterventional adverse events, primary patency at 6, 12 and 24 months, TLR rate at 24 months, predictors on reintervention, change in in clinical symptoms using the Rutherford- Becker classification (RBC), amputation and mortality rate. One hundred thirty-four patients (68.3±10.6 years, 88.8% male) were treated with a Viabahn® endoprosthesis (W.L. Gore & Associates Inc., Flagstaff, AZ, USA). Results: The average aneurysm diameter was 2.5±0.87 cm. In 41%, occlusion of the aneurysm was present. TLR rate was 31.3% and 38.8% after 12 and 24 months, respectively. Primary patency rates were 69.1%, 52.3% and 42.6% at 6, 12 and 24 months, respectively. Univariate logistic regression analysis revealed age as a predictor of reintervention and in the multivariable analysis it was treatment with lysis. An improvement in RBC was seen at all-time points. Two major amputations (1.5%) were performed and the mortality rate at 24 months was 5.2%. Conclusion: Primary patency rate after endovascular exclusion of PAA is low. However, limb salvage rate is high.